2017
DOI: 10.1016/j.appet.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-specific satiety is intact in rats made obese on a high-fat high-sugar choice diet

Abstract: Sensory-specific satiety (SSS) is the temporary decreased pleasantness of a recently eaten food, which inhibits further eating. Evidence is currently mixed whether SSS is weaker in obese people, and whether such difference precedes or follows from the obese state. Animal models allow testing whether diet-induced obesity causes SSS impairment. Female rats (n = 24) were randomly assigned to an obesogenic high-fat, high-sugar choice diet or chow-only control. Tests of SSS involved pre-feeding a single palatable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…As fructose is around twice as sweet as glucose [ 11 ], the reduced caloric intake seems to be caused by a reduced liquid intake due to a sensory-specific satiety. Sensory-specific satiety is defined as the declining pleasure and attraction to the sensory attributes to a specific food eaten in a meal [ 20 ]. Regarding to this, a glucose solution could be more pleasant to drink than a fructose solution, thus reducing the sweet-related satiety, resulting in a major consumption of glucose under same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As fructose is around twice as sweet as glucose [ 11 ], the reduced caloric intake seems to be caused by a reduced liquid intake due to a sensory-specific satiety. Sensory-specific satiety is defined as the declining pleasure and attraction to the sensory attributes to a specific food eaten in a meal [ 20 ]. Regarding to this, a glucose solution could be more pleasant to drink than a fructose solution, thus reducing the sweet-related satiety, resulting in a major consumption of glucose under same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Compulsive eating behavior is characteristic of certain forms of obesity, BED, BN, certain forms of AN, and food addiction ( de Zwaan, 2001 ; Davis and Carter, 2009 ; Gearhardt et al, 2009 ; American Psychiatric Association, 2013 ; Davis, 2013b ; Volkow et al, 2013 ; Hone-Blanchet and Fecteau, 2014 ). Compulsive eating behavior has been dissected into three functional domains: habitual overeating, eating to alleviate a negative emotional state, and overeating despite negative consequences ( Moore et al, 2017a , b , c ), engendered by maladaptive habit formation ( Furlong et al, 2014 ), the emergence of a negative affect ( Cottone et al, 2009 ; Blasio et al, 2013 ; Iemolo et al, 2013 ), and a failure of inhibitory control systems ( Velazquez-Sanchez et al, 2015 ; Nieh et al, 2015 ; Myers, 2017 ), respectively. ‘Loss of control’ is thought to result from deficits in inhibitory control mechanisms responsible for the suppression of inappropriate actions.…”
Section: Taar1 Agonism Blocks Compulsive-like Eatingmentioning
confidence: 99%
“…In a recent study, Harris confirmed our initial observations on snacking behaviour by demonstrating that the consumption of sucrose in a fluid but not solid form results in significant sucrose solution snacking behaviour during the light/inactive phase. Finally, it was recently investigated whether fc‐HFHS diet rats show altered sensory‐specific satiety, which refers to the declining pleasure and attraction to the sensory attributes of a specific food eaten in the meal relative to other foods . However, the results demonstrated that female Sprague‐Dawley made obese by long‐term maintenance on a fc‐HFHS had intact sensory‐specific satiety .…”
Section: Body Composition and Caloric Consumption Behaviourmentioning
confidence: 99%
“…Finally, it was recently investigated whether fc‐HFHS diet rats show altered sensory‐specific satiety, which refers to the declining pleasure and attraction to the sensory attributes of a specific food eaten in the meal relative to other foods . However, the results demonstrated that female Sprague‐Dawley made obese by long‐term maintenance on a fc‐HFHS had intact sensory‐specific satiety . Together, these observations suggest that the inclusion of an individual sucrose solution source drives ‘snacking’ behaviour, especially during the light/inactive phase, and that the consumption of individual fat and sugar components over‐rides the feedback signalling mechanisms normally preventing caloric overconsumption, without affecting sensory‐specific satiety.…”
Section: Body Composition and Caloric Consumption Behaviourmentioning
confidence: 99%
See 1 more Smart Citation